Measuring acute pain in the prehospital setting. Issue 8 (22nd July 2009) - Jennings, P A; Cameron, P; Bernard, S
Abstract : Severe pain is a common presenting symptom for emergency patients. One major challenge in the management of severe pain is the objective measurement of pain. Due to the subjective nature of pain, it can be very difficult for clinicians to quantify pain intensity and measure the qualitative features of the pain experience. A number of measurement tools have been validated in the acute care setting, with some appropriate for use in the prehospital setting. This paper reviews the characteristics required of a prehospital acute pain measure and appraises the relative utility of a number of currently used pain measures. At present, the verbal numerical rating scale appears the most appropriate pain measure to administer in the prehospital setting for adult patients as it is practical and valid. Either the Oucher scale or the faces pain scale is suitable for prehospital care providers to assess pain in children.